Violência sexual contra crianças e adolescentes: o balanço da arte nos anais dos Congressos Brasileiros de Assistentes Sociais de 2016 e 2019 - Silva, Lumihá Cristina Teixeira da (2021)
This study/research aims to analyze the process of production and reproduction of sexual violence against children and adolescents from historical, political and social elements built in the logic of the capitalist mode of production that exploits and expropriates the working class. The motivation for this research came from the historical process that is shaking humanity called the Covid-19 pandemic. This real, concrete fact that entered the homes of the absolute majority of the world population, expressed in one of its facets, an increase in the rate of reports of sexual violence against children and adolescents and the concern with a possible increase in underreporting in the control bodies. The investigation process was based on an exploratory study, based on qualitative and quantitative contents present in the bibliographical, documental and data research. As a general objective, we aim to analyze the state of knowledge of Social Work professionals about sexual violence against children and adolescents, based on academic productions in the annals of the Brazilian Congress of Social Workers - CBAS in 2016 and 2019. guiding question: How is the theoretical-practical understanding of sexual violence against children and adolescents manifested in the annals of the Brazilian Congresses of Social Workers?. In order to reach the general objective, we defined as specific objectives: to base the debate on sexual violence against children and adolescents from the foundations present in the work category; identify the role of the family, social protection and Social Service in confronting sexual violence against children and adolescents; discuss quantitative data, thematic focuses, understandings and trends in academic production on sexual violence against children and adolescents. The phenomenon of sexual violence against children and adolescents has been manifest over the centuries, perpetrated in society that does not see it as a possible consequence of the dispute of antagonistic class forces, but rather as an individual issue. The research took place from a critical and ontological perspective that analyzes this phenomenon in its movement within the totality, showing that sociabilities are based on political, social and economic structures that change over time. Knowing that the process of professional intervention presupposes recognizing the complexity of the demand in a perspective of totality and the contradictory terrain on which professional actions are developed, we seek to add knowledge to students and to the professional work of social workers in the country. Through this study, it was realized that violence between adults and children is an asymmetrical, hierarchical, power relationship, with the purposes of domination, exploitation and oppression, the family presents a dichotomy as a space of protection and possible violation where the greatest numbers of denouncements occur in an intramiliary context, female children constitute the largest number of victims and it is not possible to exhaust the topic, but new germs for further studies.